Angioneurotic Edema Associated with Haloperidol - Kahlon, Samrina (Hindawi Publishing Corporation, 2012)
Background. Angioneurotic edema is a life-threatening medical emergency that requires urgent diagnosis and treatment. Haloperidol is in the butyrophenone class of antipsychotic medications. Acute anaphylaxis to Haloperidol is very rare and no cases have been reported in literature. Objective. To report the association of life-threatening angioneurotic edema with intramuscular Haloperidol. Case Report. We present a case of an adult with no known allergies in whom angioneurotic edema with tongue swelling and protrusion developed after the administration of a single IM dose of Haloperidol. Conclusion. We propose angioneurotic edema in a rare side effect of Haloperidol. The onset of the symptoms is abrupt, but it may take 12–36 hours to resolve completely. Therefore patient should be monitored for 12–36 hrs.